Extensions of a Measure of Polarization with an Application to the Income Distribution of Five OECD Countries - Joan Esteban; Carlos Gradín; Debraj Ray (Luxembourg Income Study (LIS), 1999)
We introduce an extension of the Esteban and Ray [Econometrica, 1994] measure of polarization that can be applied to density functions. As a by-product we also derive the Wolfson [AER, 1994] measure as a special case. This derivation has the virtue of casting both measures in the context of a (statistically) unified framework. We study the polarization of the distribution of household income for five OECD countries (LIS database): US, UK, Canada, Germany and Sweden.
Keywords: 330; Einkommensverteilung; Disparitätsmaß; OECD-Staaten; USA; Großbritannien; Kanada; Deutschland; Schweden